Basic biology of Pneumocystis carinii: a mini review - Wanderley de Souza; Marlene Benchimol (Memorias do Instituto Oswaldo Cruz, 2005)
Basic aspects of cell biology of Pneumocystis carinii are reviewed with major emphasis on its life cycle and the structural organization of the trophozoites and cyst forms. Initially considered as a protozoan it is now established that Pneumocystis belongs to the Fungi Kingdom. Its life cycle includes two basic forms: (a) trophozoites, which are haploid cells that divide by binary fission and may conjugate with each other forming an early procyst and (b) cysts where division takes place through a meiotic process with the formation of eight nuclei followed by cytoplasmic delimitation and formation of intracystic bodies which are subsequently released and transformed into trophozoites. Basic aspects of the structure of the two developmental stages of P. carinii are reviewed.